2013
DOI: 10.1186/1471-2164-14-656
|View full text |Cite
|
Sign up to set email alerts
|

FGF2-induced effects on transcriptome associated with regeneration competence in adult human fibroblasts

Abstract: BackgroundAdult human fibroblasts grown in low oxygen and with FGF2 supplementation have the capacity to tip the healing outcome of skeletal muscle injury – by favoring regeneration response in vivo over scar formation. Here, we compare the transcriptomes of control adult human dermal fibroblasts and induced regeneration-competent (iRC) fibroblasts to identify transcriptional changes that may be related to their regeneration competence.ResultsWe identified a unique gene-expression profile that characterizes FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 71 publications
9
41
0
Order By: Relevance
“…Coupled with the in vitro data, it appears that one of the mechanisms by which FGF2 inhibits fibrosis in vivo may be via JNK-dependent activation of HGF [111]. Other reports have indicated that FGF2 upregulates HGF expression in fibroblasts as well, suggesting a degree of generality to this relationship [104, 110]. HGF has recently been implicated in the scarless wound healing phenotype of human oral mucosa fibroblasts, as knockdown of HGF was sufficient to sensitize oral mucosa fibroblasts to activation by TGF-β [112].…”
Section: Fgf2 Suppresses Pro-fibrotic Gene Expressionmentioning
confidence: 96%
See 2 more Smart Citations
“…Coupled with the in vitro data, it appears that one of the mechanisms by which FGF2 inhibits fibrosis in vivo may be via JNK-dependent activation of HGF [111]. Other reports have indicated that FGF2 upregulates HGF expression in fibroblasts as well, suggesting a degree of generality to this relationship [104, 110]. HGF has recently been implicated in the scarless wound healing phenotype of human oral mucosa fibroblasts, as knockdown of HGF was sufficient to sensitize oral mucosa fibroblasts to activation by TGF-β [112].…”
Section: Fgf2 Suppresses Pro-fibrotic Gene Expressionmentioning
confidence: 96%
“…FGF2-treated fibroblasts demonstrated decreased expression of transcripts encoding collagen I , collagen III, α-SMA, and the interstitial collagenase MMP-1 [104]. MMP-1 has also been demonstrated to be sensitive to FGF2 stimulation in varied cell types including osteoblasts and osteoblast-enriched calvariae [105107] and smooth muscle cells [108], alongside additional reports in fibroblasts [109, 110]. MMP-1 degrades interstitial collagen fibrils, including those of type I collagen, which is deposited in large quantities during the process of fibrosis.…”
Section: Fgf2 Suppresses Pro-fibrotic Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, FGF-2 stimulates fibroblast proliferation [73] and keratinocyte migration [74] in skin, while FGF-6 is increased and contributes to repair in injured skeletal muscle [75,76]. For example, FGF-2 stimulates fibroblast proliferation [73] and keratinocyte migration [74] in skin, while FGF-6 is increased and contributes to repair in injured skeletal muscle [75,76].…”
Section: Receptor For Growth Factorsmentioning
confidence: 99%
“…Aside from cancer, αvβ3 has been implicated in adult tissue regeneration and remodeling 5 , 6 . Differential expression of αvβ3 has been reported during angiogenesis, organ development, and wound healing 7 .…”
mentioning
confidence: 99%